KAJIAN PERBUATAN MELAWAN HUKUM TERHADAP WEWENANG PELAYANAN BIDAN PRAKTIK MANDIRI DI KABUPATEN BANYUMAS - Diah Arimbi (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Currently still tend to occur irregularities in the service of obstetrics. Deviations here interpreted as a midwifery services which does Not comply with code of code conduct , professional standards and law, while midwife practitioners in the fiels are trying to run the standards service. So, it can be mentioned as alleged tort. Then, related with loss due to these irregularities, the number of pain and death of both mother and baby are still the main focus in Banyumas. Mortality rate of mother and baby still high and can’t be reduced yet significantly. Midwives exceeded his authority in tort that meet elements contrary to the rights of oyhers and with the obligation of the law itself. In this case the ban is contrary to the provisions of Minister Of Health Regulation No. 1464 Year 2010 Concerning the clearance of the practice of midwives, Hospital Regulation No. 44 Year 2009 and code of ethics as well as authorize midwivesKeywords: tort law, midwev authorize, code of conduct